Fibroblasts as efficient antigen-presenting cells in lymphoid organs. - Kündig, T; Bachmann, M; DiPaolo, C; Simard, J; Battegay, M; Lother, H; Gessner, A; Kühlcke, K; Ohashi, P; Hengartner, H (1995)
Only so-called "professional" antigen-presenting cells (APCs) of hematopoietic origin are believed capable of inducing T lymphocyte responses. However, fibroblasts transfected with viral proteins directly induced antiviral cytotoxic T lymphocyte responses in vivo, without involvement of host APCs. Fibroblasts induced T cells only in the milieu of lymphoid organs. Thus, antigen localization affects self-nonself discrimination and cell-based vaccine strategies.